Black Phosphorus Nanosheet‐Based Drug Delivery System for Synergistic Photodynamic/Photothermal/Chemotherapy of Cancer. Issue 5 (24th November 2016) - Chen, Wansong; Ouyang, Jiang; Liu, Hong; Chen, Min; Zeng, Ke; Sheng, Jianping; Liu, Zhenjun; Han, Yajing; Wang, Liqiang; Li, Juan; Deng, Liu; Liu, You‐Nian; et al.
Abstract : A black phosphorus (BP)‐based drug delivery system for synergistic photodynamic/photothermal/chemotherapy of cancer is constructed. As a 2D nanosheet, BP shows super high drug loading capacity and pH‐/photoresponsive drug release. The intrinsic photothermal and photodynamic effects of BP enhance the antitumor activities. The synergistic photodynamic/photothermal/chemotherapy makes BP‐based drug delivery system a multifunctional nanomedicine platform.